2013
DOI: 10.3747/co.20.1456
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Nasopharyngeal Carcinoma: A Clinical Dilemma and Challenge

Abstract: Recurrent nasopharyngeal carcinoma, which represents a small proportion of head-and-neck cancers, has a unique set of patho-clinical characteristics. The management of recurrent nasopharyngeal carcinoma remains a challenging clinical problem. Traditional treatments offer limited local control and survival benefits; more seriously, they frequently induce severe late complications. Recently, novel treatment techniques and strategies—including precision radiotherapy, endoscopic surgery or transoral robotic resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 100 publications
2
102
0
3
Order By: Relevance
“…Cytoplasmic interaction of cyclin D1 and cyclin E with EGFR helps in cellular proliferation by the induction of progression through G1/S phase. It has been shown that endocytosis and processing of EGFR is stimulated by EBV infection; thereby the translocated processed parts of EGFR act as transcription factors inside the nucleus and further activates signaling pathways that help cell proliferation (22)(23)(24)91). In latest studies, a few cellular micro RNAs like miR17 through miR92 and miR155, are reported to be upregulated in NPC.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytoplasmic interaction of cyclin D1 and cyclin E with EGFR helps in cellular proliferation by the induction of progression through G1/S phase. It has been shown that endocytosis and processing of EGFR is stimulated by EBV infection; thereby the translocated processed parts of EGFR act as transcription factors inside the nucleus and further activates signaling pathways that help cell proliferation (22)(23)(24)91). In latest studies, a few cellular micro RNAs like miR17 through miR92 and miR155, are reported to be upregulated in NPC.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Novel treatment techniques like precision radiotherapy, endoscopic surgery, transoral robotic resection, immunotherapy, etc. are being practiced recently (18)(19)(20)(21)(22)(23)(24). Nowadays, the staging with any metastasis is diagnosed properly by the help of endoscopy, MRI, PET and CT scans; and then fusion images are formed from different modalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasopharyngeal carcinoma is generally sensitive to radiotherapy. Although with the development of medical imaging technology progress, at present the main approaches of radiotherapy for nasopharyngeal carcinoma, greatly improve the local control of nasopharyngeal carcinoma and 5 years survival rate, but frequent tumor recurrence and poor prognosis for clinical is still a great challenge [3]. The etiology of nasopharyngeal carcinoma is still unknown, and many years of research at home and abroad confirmed that nasopharyngeal carcinoma may be related to EB virus infection, environmental chemical carcinogens (such as nitrosamines) and genetic factors [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent advances in treatment techniques and strategies are providing an opportunity to potentially cure some patients with recurrent NPC. 4 Therefore, prompt identification of recurrence is of paramount importance during follow-up of patients with NPC. 5 Fluorine-18 fludeoxyglucose ( 18 F-FDG) positron emission tomography (PET) has an important role in the diagnosis and management of NPC.…”
Section: Introductionmentioning
confidence: 99%